THE VOICE OF ASIA TWO LEADERS DISCUSS THE COMING CENTURY - Mahathir Mohamad 1925-; Ishihara, Shintaro 1932- (Kodansha International, 1995)
A provocative dialogue, transcribed from meetings and written exchanges between Prime Minister Mahathir Mohamad and Japanese politician-author Shintaro Ishihara, The Voice of Asia gives unprecedented insight into what Ishihara calls "the paramount reality of the mid-1990s - the retreat of the West and the increasing dynamism of Asia." The book finds the pair in fundamental agreement.